Experimental Vortex Flow Patterns in the Primary and Secondary Pump Intakes of a Model Underground Pumping Station - Miao Guo; Zhigang Zuo; Shuhong Liu; Huijun Zou; Baoyu Chen; Deyou Li (Energies, 2020)
In order to provide specific references and suggestions for the design and operation of underground pumping stations, in this paper, an experimental model of an underground pumping station, including 4 pumps and 2 pump intakes (primary and secondary), was obtained through similitude of fluid mechanics. The phase diagrams of various vortices, in terms of different dimensionless numbers are presented, which can reveal their appearance and evolution process. Three specific cases with different vortex flows were analyzed. The experiment results may provide a reference for the current design guidelines for underground pumping stations.